Land of the ground sloths: Recent research at Cueva Chica, Ultima Esperanza, Chile - Martin, Fabiana Maria (2013)
Ultima Esperanza is a region known worldwide, where some of the best preserved remains of latePleistocene ground sloths were found. Cueva del Milodón produced a large piece of Mylodon darwini skin in 1895 as well as extensive deposits of ground sloth dung that were sampled several times during the 20th Century. These deposits are dated within 13,500 and 10,200 radiocarbon years. At Cueva del Medio, not far from Cueva del Milodón, evidence of human exploitation of extinct fauna was discovered. Also, at nearby Dos Herraduras rockshelter, several ground sloth elements were found within a tephra layer regionally dated ca. 12,600 BP. This paper presents new data derived from stratigraphic work at Cueva Chica, a site located near Cueva del Milodón, which in spite of its obvious potential was not studied previously. The work revealed more than one layer of Late Pleistocene fauna, where remains of ground sloth, a large felid and other species were preserved. Radiocarbon studies produced some of the oldest evidence for the presence of Mylodon sp. in the region. The integration of these results within the context of the paleoecology of Late Pleistocene Ultima Esperanza is presented.